Empowering Students to Prevent Sexual Harassment: The Impact of Contextual Teaching on Assertiveness through Sumbang Duo Baleh Information Services - Mimhamimdala, Fuad; Syukur, Yarmis (Universitas Ahmad Dahlan, 2025)
The increasing cases of sexual harassment, particularly among teenagers, have become a critical issue that requires immediate attention. One preventive effort is enhancing assertiveness skills, which can be improved through informational services provided by guidance and counseling teachers. This study aims to examine the effectiveness of informational services based on sumbang duo baleh using a contextual learning approach to enhance students' assertive behavior in preventing sexual harassment. The research employs a quantitative approach with a quasi-experimental method and a time-series design. The sample was randomly selected, involving one class as the experimental group, consisting of 29 female students of Minangkabau ethnicity. Data were collected using a scale measuring students' assertive behavior in preventing sexual harassment, administered as a pretest and posttest. The results show that informational services based on sumbang duo baleh with a contextual learning approach are moderately effective in improving students' assertive behavior, with an N-Gain score of 54.5% (0.5450). The percentage of students' assertive behavior increased by 12.89%, from 59.54% in the pretest to 76.61% in the posttest. Furthermore, the average score improved from 111.75 in the pretest to 176.2 in the posttest. These findings indicate that informational services based on sumbang duo baleh can serve as an effective approach to enhancing students' assertiveness as a preventive measure against sexual harassment.